(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this research was to study the component and indicator of collaborative community network for developing small sized Primary School, under jurisdiction of Basic Education Commission by using Focus Group Discussion for checking the component and indicator. Three spirals of Focus Group Discussion was implemented and concluded based on the experts’ recommendations as follows: The research findings: 1. The component of collaborative community network consisted of 4 components including: 1) the Leader, 2) Common goal, 3) Collaborative Activity, and 4) Empowerment. 2. Component 1), the Leader consisted of 3 Indicators including: Indicator 1, the Influence on the others, Indicator 2, the Order/Understood Communication, and Indicator 3, the Continuous and Good Interaction. Component 2), the Common Goal consisted of 2 Indicators including: Indicator 1, the Common View of Future Objective, and Indicator 2, the Common Perception and Comprehension in Problem. Component 3) the Collaborative Activity consisted of 3 Indicators including: Indicator 1, the Strength of Network, Indicator 2, the Strong Collaboration, Indicator 3, the Reflection of Activity Practice, and Indicator 4, the Empowerment including 2 Indicators including: Indicator 1, the Development of Strength for Network Members, and Indicator 2, the Reinforcement and Allocating the Adequate Resource.